Green Polymorphic Cooperative Formation Strategy of Low-Carbon Unmanned Surface Vessels - Yuzhou Lu; Qihe Shan; Geyang Xiao; Yuan Liang; Wei Liu (Frontiers in Energy Research, 2022)
At the current stage of a global energy shortage, the optimization of marine energy consumption has received attention. In order to save marine energy consumption and reduce pollution, research on low-energy-consumption Unmanned Surface Vessels (USVs) and their green and low-carbon cooperative operation methods needs to be paid attention to. Due to the ever-changing environment of USVs in actual sea conditions and the increasingly complex tasks, the cooperation of a single swarm of USVs is incompetent. First, in order to cope with larger-scale and complex tasks, we construct the multilateral cooperative control system for USVs with topology scalability under a polymorphic network and propose the multilateral distributed control protocol. Second, in order to reduce the energy consumption of the cooperative operation of USVs, the low-energy-consumption and low-carbon USVs are selected with the lowest EEOI index as the optimization goal, and based on ad hoc on-demand distance vector routing (AODV), the optimal path between USVs is obtained. Then, the swarms are grouped by External Equitable Partition (EEP), and the green autonomous cooperative formation strategy is proposed. Finally, the simulation examples are used to verify the effectiveness of the method proposed in this article.